The Effect of Good Corporate Governance on Earnings Quality Banking Companies Listed on the IDX for 2010-2019 - Siahainenia, Johan Pratama (International Journal of Review Management Business and Entrepreneurship (RMBE), 2022)
This study aims to examine the effect of Good Corporate Govenance (through CEO Duality,Board Size, Board Composition, and Audit Committee) on Earning Quality in conventional banking companies, with firm size as a control variable. The data used in this study are financial statement for the period 2010 – 2019. The analytical method used is panel data regression analysis using E – Views software. The population in this study were conventional banking companies listed on IDX in the period 2010 – 2019with a sample size of 26. This study found that Board Composition had a significant effect on Earnings Quality, while CEO Duality, Board Size, and Audit Committee had no significant effect on Earnings Quality. This Study also founf that Firm Size was not able to control the effect of CEO Duality, Board Size, Board Composition, and Audit Committee on Earnings Quality.